Effect of co-application of phosphorus fertilizer and in vitro-produced mycorrhizal fungal inoculants on yield and leaf nutrient concentration of cassava - Aliyu, I.A.; Yusuf, A.A.; Uyovbisere, E.O.; Masso, C.; Sanders, I.R. (Public Library of Science, 2019)
The adaptability of cassava to low fertile and marginal soils facilitates its production in subsistent agriculture. As a result, smallholder farmers rarely apply fertilizers. The current yield gap is therefore very large, calling for application of fertilizers and soil amendments to improve its productivity. Field experiments were carried out to assess the potential of partially substituting Phosphorus (P) fertilizers by in vitro-produced arbuscular mycorrhizal fungal (AMF) inoculants in cassava production in two agro-ecologies of Nigeria: Northern Guinea Savanna (Samaru) and Sudan Savanna (Minjibir). The experiments were laid out in a split plot design with P levels (0, 17.5, 35 and 52.5 kg P2O5 ha-1) as main plot and AMF inoculants (Control, Glomygel, Glomygel carrier, Mycodrip, Mycodrip carrier) as subplots. The results in Samaru showed that there was significant interaction between AMF and P in root fresh weight, total biomass and root to shoot ratio. The root fresh weights of the inoculated cassava increased proportionally with application of P. However, highest root fresh weight of cassava inoculated with Glomygel was observed at 35 kg P2O5 ha-1 recording 25% yield increase compared to 52.5 kg P2O5 ha-1 application. Interestingly, Cassava inoculated with Glomygel at 17.5 kg P2O5 ha-1 gave root fresh yield statistically similar to where 35 kg P2O5 ha-1 was applied. This represented a 50% reduction in P fertilizer use. Also, cassava inoculated with Glomygel increased leaf nutrient concentrations, which strongly correlated with the root fresh yield. However, no effects of inoculant carriers were observed in yield and nutrient concentrations. Contrarily, there was no significant treatment effect in Minjibir for nearly all the measured parameters. Cassava yield was however, higher in Minjibir than Samaru probably due to soil fertility and structural differences, which resulted in few observable effects of AMF and P treatments at Minjibir. We conclude that under low P conditions inoculation with in vitro produced AMF inoculants could be employed to reduce P fertilizer requirements for cassava and improve yields, but the variability of the responses as a result of soil heterogeneity and the identity of the fungal strain in the inoculant require further investigations before recommending the practice.